Tourism Services Contract in Russia and the United States - SAVTSOVA, Natalya Aleksandrovna; VOLKOVA, Maria Alexandrovna; BOGMATSERA, Eduard Victorovich; LUTOVINOVA, Natalya Viktorovna (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019DO - 10.14505//jemt.v10.6(38).07, 2019)
This article discusses the features of concluding contracts in the field of tourism services. The purpose of the article is to consider the contract as a form of implementation of tourism services. The authors have analyzed the practice of Russia and the United States in this area. Special attention has been paid to the specifics of these legal relations, as well as the directions of using foreign experience in the activities of national tourism companies. As a result, it has been concluded that legal regulation of the contract for rendering tourism services in these countries is somewhat similar. However, in Russia, this institution is regulated at the federal level and in more detail, which indicates the greater effectiveness of Russian legislation in this area. It has been proposed to make some changes and additions to the current Russian legislation in order to more fully regulate this institute.